Perancangan Website Bakohomas Diskominfo Provinsi Jambi - Aidil Irfandi; Mohammad Brian Pramudya; Rahmat Hidayat; Mubasyir Mubarak; Saldi Yulistian (Departement of Mathematics Education, 2023)
Bakohumas is a non-structural institution which is a coordination and cooperation forum between work units in the ministry of public relations, non-ministerial government agencies, public broadcasting institutions, non-structural state institutions, provincial and district/city regional governments. At this time the Jambi Provincial Communication and Informatics Service does not yet have an official website regarding these Bakohumas activities, the delivery of information is still through the WhatsApp grou4p, so that the delivery of information and activities tends to be slow and inefficient, this is one of the obstacles to implementing Bakohumas activities. The purpose of this research is to create a company profile information system that can assist in the Communication and Informatics Office of Jambi province. The practical performance methodology used is observation and interview methods. In making the Bakohumas Website using PHP as the program and MySQL as the database.